Short Segment Spinal Instrumentation in Early-onset Scoliosis Patients Treated With Magnetically Controlled Growing Rods Surgical Technique and Mid - Short-term Outcomes - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2017)
Study Design. A prospective, a single-institution, nonrandomized study. Objective. The aim of this study was to evaluate the safety and effectivity of short-segment instrumentation in early-onset scoliosis (EOS) patients treated by magnetic-controlled growing rods (MCGRs). Summary of Background Data. Despite the common use of conventional growing rods and the recent popularity of MCGR in the treatment of progressive EOS, distal instrumented vertebra and number of the spanned levels are not standardized. Methods. Patients with progressive EOS, characterized by the major thoracic curve and nonstructural compensatory curve, were a candidate to be treated by dual MCGR short segment spinal instrumentation spanning the major thoracic curve; such patients are followed up for a minimum period of 30 months. Radiological data were collected and analyzed in terms of Cobb angle of both primary and secondary curve, kyphosis angle, T1-T12, and T1-S1 distances, and T1-T12/T1-S1 ratio in preoperative, postoperative, and last follow-up. Results. Sixteen patients with different diagnoses of EOS, mean age at the operation was 7 years and 10 months (5 years and 6 months-9 years and 10 months), and mean period of followup was 37 (30-54) months. The Cobb angle of both major and compensatory curve are corrected by the mean value of 628 (44-85), 358 (22-45) preoperatively to 298 (12-49), 148 (9-24) postoperatively, and maintained at 28 degrees (10-47), 10 degrees (2-20) in the last follow-up, respectively. The T1-T12/T1-S1 ratio was 0.58 preoperatively, 0.6 postoperatively, and 0.62 at the last follow-up. The average yearly T1-T12 and T1-S1 length increase were calculated as 7 and 9 mm/year, respectively. Conclusion. Selective fusion principals are applicable to EOS, in that short segment instrumentation with MGCR in thoracic curve EOS patients is an effective technique in correction of both structural and compensatory curve, and in maintaining the correction during subsequent nonsurgical spinal distraction.
Keywords: early-onset scoliosis; EOS; instrumentation level; magnetic-controlled growing rod; MCGR; selective fusion; short segment; ADOLESCENT IDIOPATHIC SCOLIOSIS; THORACIC FUSION; MOTION; SELECTION; VERTEBRA; GROWTH